2011
DOI: 10.2319/071910-420.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of incisor position and dental transverse dimensional changes using the Damon system

Abstract: Objectives: To test the hypotheses that the Damon system will maintain intercanine, interpremolar, and intermolar widths. To test subsequent hypotheses that the Damon system will not produce a significant difference in maxillary and mandibular incisor position/angulation when compared with control groups treated with conventional fixed orthodontic appliances for similar malocclusion. Materials and Methods: Subjects treated with the Damon system (N 5 27) were compared with subjects treated with a conventionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
56
5
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 11 publications
9
56
5
16
Order By: Relevance
“…Between the two groups, there was a slight absolute mean difference of 0.33 mm increase in the conventional group arch width; however, this was not statistically significant (Table 3). In contrast to our findings, both Pandis et al 21 and Vajaria et al 22 found a greater intermolar arch width increase in patients treated with the Damon system than in the conventional edgewise group. This difference might be partly explained in the Pandis et al article by the use of rectangular Cu-NiTi arch wires in the Damon group, while using only round NiTi in the conventional group.…”
Section: Discussioncontrasting
confidence: 56%
“…Between the two groups, there was a slight absolute mean difference of 0.33 mm increase in the conventional group arch width; however, this was not statistically significant (Table 3). In contrast to our findings, both Pandis et al 21 and Vajaria et al 22 found a greater intermolar arch width increase in patients treated with the Damon system than in the conventional edgewise group. This difference might be partly explained in the Pandis et al article by the use of rectangular Cu-NiTi arch wires in the Damon group, while using only round NiTi in the conventional group.…”
Section: Discussioncontrasting
confidence: 56%
“…Their results were very similar to those obtained in the current study. Similar to our results, Vajaria et al 5 and Jiang and Fu 7 indicated that both the conventional and Damon bracket systems cause labial inclination of the incisors. These results emphasize that two different treatment systems proclined maxillary and mandibular incisors in a similar manner, which agrees with the results of our study.…”
Section: Discussionsupporting
confidence: 82%
“…In both systems, the arch widths were significantly larger after the treatment (Table 4). Pandis et al 9,13 and Vajaria et al 5 reported greater intermolar arch width increases in patients treated with the Damon system than in conventional treatment groups. However, these studies did not use active expansion appliances before fixed-appliance therapy in the conventional group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations